Energy-efficient Hardening of the SEDIMENT Methodology for Scalable IoT Network Security - Shur, D.; Di Crescenzo, G.; Chen, T.; Patni, Z.; Lin, Y-J.; Alexander, S.; Flin, B.; Levonas, R. (2024 IEEE International Conference on Cyber Security and Resilience (CSR), 2024)
Advances in wireless networking, including 5G and beyond, continue to enable the vision of the Internet of Things (IoT), with an impressive number of connected IoT devices, collecting much data and making it available to interested parties (i.e., application servers). This vision poses important challenges with respect to performance, due to the limited device resources and scalability needs, and security, as demonstrated by recent events such as botnet attacks (e.g., [1). In this paper we revisit our previous system and methodology, called SEDIMENT, for scalable IoT network security, based on the following main ingredients: root of trust, remote attestation and end-to-end-secure publish-subscribe, while using resource-efficient cryptography algorithms and support of zero-trust principles. We ask the question of whether this system can maintain the same IoT device energy efficiency properties when subject to substantial attack activity. We positively answer this question by applying a number of hardening techniques and showing that hardened SEDIMENT maintains device energy efficiency, as substantiated with experiment results and analysis, for the following large set of attacks: eavesdropping, spoofing, replay, man in the middle, misbehaving publishers, misbehaving subscribers, malformed inputs and DoS on IoT devices.